Kato Nan Ampek Dalam Tambo Alam Minangkabau Karya Ibrahim Dt. Sanggoeno Diradjo: Analisis Hermeneutika Wolf - Muharram, Syahrul; Burhanuddin, Nunu (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The purpose of the study is to find out the meaning of kato nan ampek in the Minangkabau tradition in the book "Tambo Alam Minangkabau" based on Friedrich Augus Wolf's Hermeneutics. The results of this thesis are: first, Kato Nan Ampek in the book Tambo Alam Minangkabau, this kato nan ampek can be said to be jalan nan ampek in Minangkabau philosophy. So that kato nan ampek becomes the philosophy of the Minangkabau people. Second, kato nan ampek is seen or analyzed based on Friedrich August Wolf's hermeneutics: (1) Grammatically kato nan ampek has a meaning that is associated with the meaning of local culture such as walking. This means that it is adjusted to conditions and attitudes. (2) Historically Kato Nan Ampek does not exist in data that proves when, where, who created the term. But it appears orally which has been passed down from generation to generation or is in Tambo. (3) Philosophically, kato nan ampek has a relation, connection, value with Minangkabau culture, namely raso, pareso, malu, and politeness. Because the philosophy of the Minangkabau people also comes from the term "Alam Takambang Jadi Guru". In the book Tambo Alam Minangkabau by Ibrahim Dt Sanggoeno Diradjo. That kato nan ampek was born in connection with Tambo in Minangkabau which originated from Adaik basandi syarak, Syarak basandi Kitabullah, Syarak mangato, Adaik mamakai, Kawi kato syarak, Lazim kato adaik. This also means that people in Minangkabau understand and know the etiquette and politeness of acting and speaking.